(untitled) (Revista de História da UEG (REVHIST), 2022)
Although generally not known by public and only briefly addressed by historians, the so-called "Forgotten Revolt" stands out among urban conflicts in Brazilian history, given the chaotic scenario that the movement caused. This article explores the 1924 Paulist Revolt, discussing the historical context of the early 1920s, political and military events, consequences of the movement, and the relevance of this theme in the scope of Brazilian historiography. Although generally not known by public and only briefly addressed by historians, the so-called "Forgotten Revolt" stands out among urban conflicts in Brazilian history, given the chaos the movement caused. The episode registered bombings, shootings, looting, mass urban exodus and thousands of deaths and injuries, in addition to the destruction of several buildings, homes and commercial establishments in the city of São Paulo. The 1924 Revolt was part of the Brazilian tenentista movement of the 1920s, which sought to turn away from the oligarchic policy of the Old Republic. Thus, this article will seek to rescue the memory of this important event in the history of Brazil, which has been overshadowed for several reasons. Keywords: Historiography. Revolt. São Paulo. Tenentismo.